Fyra trädgårdar på bjälklag - Lundbladh, Karolina (2009)
This thesis discusses issues relating to the design and construction of roof gardens. The focus is on whether roof gardens constitute a specific habitat which demands plant material with certain characteristics, and on how the design of a roof garden can be affected by the underlying joist construction. The result is based on a comparative case study of four projects in Malmö and Copenhagen.Each project has been studied through visits, reviews of the construction drawings and interviews with the landscape architect behind the project. Subsequently the projects were discussed, analyzed and compared with each other.